Table of Contents - Board, Editorial (Law, State and Telecommunications Review, 2023)
We are delighted to include articles on Kazakhstan’s electronic money trends and the need legal reforms for its proper functioning and circulation; the evolution of regulatory debates on internet interoperability and network access through case studies from the United States and Europe; the right to be forgotten in digital law, with a focus on European Union Court of Justice and European Court of Human Rights decisions; the legal solutions for defining robots in civil relations and establishing effective regulations for robotics usage in Ukraine; the use of artificial intelligence in the Ukrainian Judicial System; the legal aspects of digital face identification technology in criminal proceeding in Ukraine, China’s artificial intelligence-driven social credit system’s impact on international human rights, particularly concerning privacy issue; the role of electronic money in modernizing Kazakhstan’s monetary system; the development of a cyber-crime protection system in Indonesia, including cyber insurance regulations; the impact of digital transition and its intensification during crises like the COVID-19 Pandemic and the Ukraine War on the tourism industry in the European Union; the prevention of cyber sabotage in Ukraine and the control of its damages; and the standardization of cybersecurity threat terminology on a global scale.